International organisation: world politics - "Cox, Robert W.(ed.)" (London, 1969)
The editor introduces the collection with an essay on the state and trends of studies about international organisation-the problems dealt with and perspectives and methods adopted - and concludes with a prospective view of possible future functions of international organisations The analyses made in the different chapters lead um towards the conclusion that international organisation will during the years to come reflect and reinforce two contradictory trends in world
Keywords: World politics